Institutions that educate: Geography teacher's education during the emergence of brazilian universities - Lucas Ferraz Frauches Carvalho; Rafael Straforini (Universidade Federal de Santa Catarina, 2018)
Prior to the curriculum reform implemented by the Conselho Nacional de Educação (CNE) in 2002 which affected the teacher education, the curricular logic in place at universities was known as the "3+1" structure: three years dedicated to specific knowledge from the students' area of performance (in this case, geography), and another year dedicated to pedagogical knowledge. In this article, we will reflect about the discourses regarding teachers' formation imbued into these first three years of the "3+1" curriculum during the time higher education geography courses were being designed, from an archeology of knowledge's methodological standpoint. Therefore, if the teacher is formed by the curriculum, or rather if the curriculum constitutes the teacher through a process of subjectification, understanding the geographic knowledges spread across the institutions that produce them (schools, universities and geography societies) becomes necessary